A Functional Slow Recycling Pathway of Transferrin is Required for Growth of Chlamydia - Ouellette, Scot; Carabeo, Rey (Frontiers in Microbiology, 2010)
An inhibitor of host cell lysophospholipid acyltransferase, an enzyme involved in lipid metabolism blocked growth of the obligate intracellular pathogen Chlamydia through its action on the transport of transferrin (Tf) via the slow pathway of recycling. A detailed characterization of this inhibition revealed that Tf accumulated in vesicles positive for Rab11, with a concomitant reduction in the level of Tf found within the transport intermediate Rab4/11 hybrid vesicles. The net result was the failure to be recycled to the plasma membrane. In chlamydiae-infected cells, the Tf-containing Rab11-positive vesicles were typically found intimately associated with the inclusion, and treatment with the inhibitor caused their accumulation, suggesting that the timely progression and completion of Tf recycling was necessary for proper chlamydial growth. Growth inhibition by the compound could be negated by the simple removal of the Tf-containing fraction of the serum, a further indication that accumulation of Tf around the chlamydial inclusion was deleterious to the pathogen. Thus, it appears that manipulating the slow recycling pathway can have biological consequences for Chlamydia and implies the need to regulate carefully the interaction of the inclusion with this host trafficking pathway.